Formal Methods: Foundations and Applications 13th Brazilian Symposium on Formal Methods, SBMF 2010, Natal, Brazil, November 8-11, 2010, Revised Selected Papers - Davies, Jim.; Silva, Leila; Simao, Adenilso; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the 13th Brazilian Symposium on Formal Methods, SBMF 2010, held in Natal, Brazil, in November 2010. The 18 revised full papers were carefully reviewed and selected from 55 submissions. The papers presented cover a broad range of foundational and methodological issues in formal methods for the design and analysis of software and hardware systems as well as applications in various domains.
Keywords: Computer science; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Programming Languages, Compilers, Interpreters; Programming Techniques; Mathematical Logic and Formal Languages; Management of Computing and Information Systems